Workforce Diversity Impact on Civil Servant's Performance: Motivation and Commitment as Mediator - Hannana, Dena Maulidi; Khan, Ryan Basith Fasih (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
This research aims to determine the impact of workforce diversity on employee performance by using work motivation and organizational commitment as mediating variables in State Civil Service Employees in Batu City. This research method uses a quantitative approach using the Explanatory Research method, which aims to explain the position of the variables that have been investigated and the relationship between one variable and other variables. Samples were taken using saturated sampling techniques, and data collection was carried out by distributing questionnaires online via Google Forms. The data analysis technique uses the Partial Least Square method using Smart PLS 4.0 Software. The research shows that workforce diversity is considered capable of positively and significantly influencing employee performance. This research also provides an understanding of the role of Work Motivation and Organizational Commitment as Mediating Variables in the relationship between Workforce Diversity and Employee Performance. This research confirms that workforce diversity has been managed well through various programs prepared inclusively, providing awards, recognition, and fair treatment. This aims to ensure that the needs of each employee can be met without discrimination and exceptions.